2017
DOI: 10.1016/j.jjcc.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of moderate to severe renal impairment on long-term clinical outcomes in patients with atrial fibrillation

Abstract: Moderate to severe renal impairment is a poor prognostic factor of long-term clinical outcomes in AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…OAC could reduce 30-day mortality in AKI patients with AF in our study. Similarly, a retrospective observational study reported that moderate to severe renal impairment increased ischaemic stroke risk in AF patients not receiving antithrombotic treatments 17. Since the benefit of OAC is strongly related to the CHA2DS2-VASc score, subjects with lower CHA2DS2-VASc scores also had a decreased risk of mortality by using OAC in our study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…OAC could reduce 30-day mortality in AKI patients with AF in our study. Similarly, a retrospective observational study reported that moderate to severe renal impairment increased ischaemic stroke risk in AF patients not receiving antithrombotic treatments 17. Since the benefit of OAC is strongly related to the CHA2DS2-VASc score, subjects with lower CHA2DS2-VASc scores also had a decreased risk of mortality by using OAC in our study.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, a retrospective observational study reported that moderate to severe renal impairment increased ischaemic stroke risk in AF patients not receiving antithrombotic treatments. 17 Since the benefit of OAC is strongly related to the CHA2DS2-VASc score, Open access subjects with lower CHA2DS2-VASc scores also had a decreased risk of mortality by using OAC in our study. This may be due to the higher rates of thromboembolism and bleeding in patients with the deterioration of renal function, 5 18 but the absolute benefits of OAC in this population outweigh the risks, and OAC should be considered for AKI patients with AF.…”
Section: Discussionmentioning
confidence: 56%
“…In our cohort, the proportional of hypertension increased along with decreasing CrCl, up to 70.5% in the CrCl < 30 ml/ml group. Previous study showed that left ventricular EF decreased and left atrial size increased in the eGFR < 60 ml/min group (Cho et al, 2017 ). And our study showed higher proportion of DM, CAD, and previous stroke, which may affect the outcome.…”
Section: Discussionmentioning
confidence: 82%
“…The presence of renal dysfunction in AF patients was associated with a substantial increase in TE incidence and an increased risk of bleeding events (Potpara et al, 2018 ). Previous studies already demonstrated that moderate to severe renal impairment increased the risk of bleeding in AF patients (Abe et al, 2017 ; Banerjee et al, 2014 ; Cho et al, 2017 ; Yuzawa et al, 2020 ), but some other studies showed diffident results, renal impairment was not a risk factor for bleeding (Boriani et al, 2016; Kodani et al, 2018 ). This study showed renal dysfunction was not an independent predictor for major bleeding.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation